2017
DOI: 10.1093/humrep/dew355
|View full text |Cite
|
Sign up to set email alerts
|

Response to ovarian stimulation is not impacted by a breast cancer diagnosis

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 36 publications
7
65
1
5
Order By: Relevance
“…Recently, a few studies have demonstrated a potential benefit of the use of the oral agent letrozole together with gonadotropin stimulation in IVF cycles, especially in breast cancer patients going through fertility preservation treatment 12 15 . The goal of co-administration of letrozole is to reduce serum estrogen concentrations during ovarian stimulation in breast cancer patients.…”
Section: Improving Oocyte Quality With New Stimulation and Triggeringmentioning
confidence: 99%
“…Recently, a few studies have demonstrated a potential benefit of the use of the oral agent letrozole together with gonadotropin stimulation in IVF cycles, especially in breast cancer patients going through fertility preservation treatment 12 15 . The goal of co-administration of letrozole is to reduce serum estrogen concentrations during ovarian stimulation in breast cancer patients.…”
Section: Improving Oocyte Quality With New Stimulation and Triggeringmentioning
confidence: 99%
“…Only two studies reported worse oocyte yield in comparison to women without cancer undergoing IVF ( Klock et al ., 2010 ; Domingo et al ., 2012 ). Quinn et al (2017) published a retrospective cohort analysis with 589 women (191 with breast cancer) who underwent COS. The group with breast cancer responded as well as the ones without cancer in terms of number of mature oocytes obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the limited data on the efficacy of oocyte cryopreservation specifically in the oncological population, the response to controlled ovarian stimulation could be considered the same as the non-cancer population. 64 The success of oocyte/embryo cryopreservation is strongly dependent on the number of mature oocytes collected following controlled ovarian stimulation which is strongly influenced by the age and ovarian reserve of the patient at the time of the procedure. 65 The live birth rates using all cryopreserved oocytes after one stimulation cycle are around 35% in women <35 years.…”
Section: Fertility Preservation In Male Patients With Cancer Sperm Crmentioning
confidence: 99%